The Quality of Life and Its Relationship With Systemic Family Dynamics and Mental Health in Senior High School Students From Shaanxi, China - Zhe Yang; Yijiang Shang; Ying Liang; Haiyue Zhang; Yifan Yang; Yue Wang; Lei Shang; Yuhai Zhang (Frontiers Media S.A., 2022)
ObjectiveTo explore the quality of life (QoL) status of senior high school students in the Shaanxi Province and the relationship of the QoL with systemic family dynamics and mental health.MethodsThis was a cross-sectional observational study in a sample of 1,402 senior high school students; students were asked to complete a questionnaire which comprised the 36-item Short Form Health Survey (SF-36) to assess the QoL, the Self-rating Scale of Systemic Family Dynamics (SSFD) for assessing family functioning, the Symptom Checklist-90-Revised (SCL-90-R) for assessing mental health and general demographic variables.ResultsGrades of senior high school students were defined as Grade 1 (first year), Grade 2 (second year), and Grade 3 (third year). Compared to Grade 3 students, Grade 1 students had higher scores in physical functioning, role-emotional, bodily pain, and reported health transition of the QoL over the last 1 year (P < 0.05). Multiple linear regression showed that the place of residence, subscales of systemic family dynamics, somatization, and depression significantly affected the total QoL score. The results of SEM show that the SCL-90-R score fully mediated the association between the SSFD score and SF-36 score (indirect effect coefficient 0.055; 95% CI, 0.012-0.106; P = 0.042).ConclusionThe QoL score of senior high school students was low, particularly that of Grade 3 students, who consequently need more emotional support. By improving and enhancing systemic family dynamics, the QOL of high school students will improve and discovering and addressing their mental health problems will be easier.